Intense seismicity during the 2014–15 Bárðarbunga-Holuhraun rifting event, Iceland, reveals the nature of dike-induced earthquakes and caldera collapse mechanisms - White, Robert; Agustsdottir, Thorbjorg; Winder, Tom; Woods, Jennifer; Greenfield, Tim; Brandsdottir, Bryndis (Wiley-Blackwell, 2019)
Over two weeks in August 2014 magma propagated 48km laterally from Bárðarbunga volcano before erupting at Holuhraun for 6 months, accompanied by collapse of the caldera. A dense seismic network recorded over 47,000 earthquakes before, during and after the rifting event. More than 30,000 earthquakes delineate the segmented dike intrusion. Earthquake source mechanisms show exclusively strike-slip faulting, occurring near the base of the dike along pre-existing weaknesses aligned with the rift fabric, while the dike widened largely aseismically. The slip-sense of faulting is controlled by the orientation of the dike relative to the local rift fabric, demonstrated by an abrupt change from right- to left-lateral faulting as the dike turns to propagate from an easterly to a northerly direction. Approximately 4,000 earthquakes associated with the caldera collapse delineate an inner caldera fault zone, with good correlation to geodetic observations. Caldera subsidence was largely aseismic, with seismicity accounting for 10% or less of the geodetic moment. Approximately 90% of the seismic moment release occurred on the northern rim, suggesting an asymmetric collapse. Well-constrained focal mechanisms reveal sub-vertical arrays of normal faults, with fault planes dipping inward at 60 9 , along both the north and south caldera margins. These steep normal faults strike sub-parallel to the caldera rims, with slip vectors pointing towards the center of subsidence. The maximum depth of seismicity defines the base of the seismogenic crust under Bárðarbunga as 6km b.s.l., in broad agreement with constraints from geodesy and geobarometry for the minimum depth to the melt storage region.